The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/ccm.0000000000000613
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of Patients’ and Caregivers’ Experiences of Severe Sepsis*

Abstract: The study extends what was understood about severe sepsis from the patients' and caregivers' perspectives from the previous limited literature. Caregivers as well as patients reported enduring impact. The study also identified problems of lack of awareness of diagnosis and understanding of severe sepsis by patients and caregivers and difficulties accessing appropriate healthcare providers and ancillary services after discharge from hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
72
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 20 publications
3
72
1
2
Order By: Relevance
“…Without longitudinal data between hospital discharge and the time of the interview, it is plausible that other events explain the impairments identified, and the rates of symptom remission and functional recovery require direct examination. Also, although our results are consistent with the existing literature (18,19,59), we acknowledge the potential for recall bias regarding our qualitative analyses. Specifically, the ordering of the interview, with objective assessments followed by open-ended questions, may have resulted in a framing bias in terms of responses elicited.…”
Section: Original Researchsupporting
confidence: 82%
See 2 more Smart Citations
“…Without longitudinal data between hospital discharge and the time of the interview, it is plausible that other events explain the impairments identified, and the rates of symptom remission and functional recovery require direct examination. Also, although our results are consistent with the existing literature (18,19,59), we acknowledge the potential for recall bias regarding our qualitative analyses. Specifically, the ordering of the interview, with objective assessments followed by open-ended questions, may have resulted in a framing bias in terms of responses elicited.…”
Section: Original Researchsupporting
confidence: 82%
“…To augment existing support networks, peer support is another potentially valuable intervention (57,58) that could complement a redesign of multidisciplinary follow-up care that aims to better support survivors and their family and caregivers. Consistent with the qualitative experience of survivors of acute respiratory distress syndrome and sepsis (18,19,59), clinicians have a profound therapeutic impact on survivors during recovery in terms of their ability to reassure, educate, rehabilitate, prepare, and support survivors for life after critical illness. The ICU diary is one novel strategy to personalize this process and improve longterm neuropsychological health (60,61).…”
Section: Original Researchmentioning
confidence: 88%
See 1 more Smart Citation
“…Relatives' qualitative accounts discuss the impact and causes of psychological stress. Relatives described feeling overwhelmed by anxiety and stress related to their role as a caregiver (Söderström et al ., ; Ågård et al ., ; Gallop et al ., ). Many cited intense feelings of fear of the future and uncertainty about becoming a caregiver (Söderström et al ., ; Ågård et al ., ; Frivold et al ., ).…”
Section: Health and Well‐beingmentioning
confidence: 88%
“…Thirteen studies reported moderate to severe depressive symptoms in 20–43% of relatives 2 to 3 months after ICU discharge (Van Pelt et al ., ; Douglas et al ., ; Lemiale et al ., ; Choi et al ., ; McAdam et al ., ; Hwang et al ., ; Sundararajan et al ., ; Andresen et al ., ; Gallop et al ., ; Cameron et al ., ; McPeake et al ., ; Warren et al ., ). Cameron et al .…”
Section: Health and Well‐beingmentioning
confidence: 97%